Cobalt Oxide on Boron-Doped Graphitic Carbon Nitride as Bifunctional Photocatalysts for CO2 Reduction and Hydrogen Evolution - da Cruz, Jean C.; da Silva, Gelson T. S. T.; Dias, Eduardo H.; Lima, Diego S. D. [UNESP]; Torres, Juliana A.; da Silva, Pollyana F.; Ribeiro, Caue (American Chemical Society (ACS), 2024)
In this work, the prepared cobalt oxide decorated boron-doped g-C3N4 (CoOx/g-C3N4) heterojunction exhibits remarkable activity in CO2 reduction (CO2RR), resulting in high yields of CH3COOH (∼383 μmol·gcatalyst-1) and CH3OH (∼371 μmol·gcatalyst-1) with 58% selectivity to C2+ under visible light. However, the same system leads to high H2 evolution (HER) by increasing the cobalt oxide content, suggesting that the selectivity and preference for the CO2RR or HER depend on oxide decoration. By comparing HER and CO2RR evolution in the same system, this work provides critical insights into the catalytic mechanism, indicating that the CoOx/g-C3N4 heterojunction formation is necessary to foster high visible light photoactivity.
Keywords: acetic acid; CO2 photoreduction; cobalt oxide; g-C3N4; hydrogen